The effect of local own-source revenue and balancing funds on regional expenditures: A study of East Kalimantan regional expansion - Zaki Fakhroni; Irwansyah Irwansyah (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
This study aims to examine the effect of local own-source revenue and balancing funds on regional expenditures and to find out the differences before and after the province expansion. This study uses the performance report of regional/municipal government agencies in North Kalimantan from 2008 to 2017 as the data. The data were analyzed using the SmartPLS 3.0 program. From the test results, it is shown that: 1) Local own-source revenue has a positive and significant effect on regional expenditures, 2) Balancing funds have a positive and significant effect on regional expenditures, 3) There are differences in the effect of local own-source revenue on regional expenditures before and after the regional expansion, and 4) There is no difference in the influence of balancing funds on regional expenditures before and after regional expansion.